Efektivitas Penggunaan Buku Saku Higiene Menstruasi dan Pencegahan Kekerasan dalam Situasi Bencana Pada Remaja Putri - Lita Angelina Saputri; Iin Prima Fitriah; Yussie Ater Merry (Jurnal Kebidanan dan Kesehatan Tradisional, 2020)
Background: Menstruation hygiene and violence in disaster situation can cause serious problems for adolescent girls. Poor menstrual hygiene during disaster can increase the risk of reproductive tract infections and violence can lead to unwanted pregnancy, abortion and psychological trauma. Approximately 80% of the needs of adolescent girls are not met during disaster. They need to be prepared to be able to empower themselves in dealing with disaster situations. Pocket book is one of the media to increase knowledge. The purpose of this study was to determine the effect of the use of menstrual hygiene pocket books and prevention of violence in disaster situations on the knowledge of adolescent girls. Methods: This research method is pre experiment with one group pre test and post test design. The study was conducted in May to October 2019 at SMAN 7 Lubuk Buaya Padang with 51 respondents using proportionate random sampling. Research instrument using questionnaire. Univariate and bivariate data analysis used Chi Square with 95% confidence level. Results: There is a significant effect of the use of pocket book on the knowledge of adolescent girls about menstrual hygiene and prevention of violence in disaster situations (p=0,000). Conclusion: It is hoped that the school can utilize the pocket book to increase the knowledge and preparedness of adolescent girls in dealing with disaster situations.